Effect of Feeding Sugarcane Molasses Based Distilleries Raw Spent Wash on Growth Performance, Nutrient Utilization and Blood Biochemical Parameters in Heifers - Kesharwani, Pradeep Kumar; Kumar, Vinod; Roy, Debashis; Kumar, Muneendra; Singh, Shankar Kumar; Kushwaha, Raju; Vaswani, Shalini (Indian Journal of Animal Nutrition, 2018)
The objective of this study was to evaluate the molasses based raw spent wash as an alternative energy feed substitute in heifers. The study was conducted in two phases. In phase I, effect of replacement of 0, 5, 10, 15 and 20% of substrate with raw spent wash was studied on in vitro DM digestibility (IVTDMD), in vitro OM digestibility (IVTOMD), pH, in vitro gas production, partitioning factor (PF), total volatile fatty acid (TVFA),ammonia nitrogen (NH3-N) and microbial biomass production (MBP). Results revealed that there was no significant effect of incorporation of different levels raw spent wash on gas production, TVFA production and NH3-N. IVTDMD and IVTOMD digestibility and MBP showed positive correlation with raw spent wash levels. In phase II, eighteen heifers were randomly allocated into three groups (n=6) for a period of 150 d on bodyweight basis. Feeding regimen was similar in all the groups except that the 10 and 20% barley grains of concentrate mixture were replaced with raw spent wash (RSW). Inclusion of 10 and 20% RSW did not alter feed intake, growth performance and nutrient digestibility among groups. The levels of haemoglobin, packed cell volume, total protein, globulin, alanine transaminase, aspartate amino transferase, alkaline phosphatase, plasma urea nitrogen, Ca, P, Mg, ferric reducing antioxidant power assay and non esterified fatty acids. A higher (P